Design method of serviceability limit states of BFRP bar reinforced ecological high ductility concrete beam: Experimental and theoretical analysis. (June 2022) - Chai, Li-Juan; Guo, Li-Ping; Chen, Bo; Sun, Peng-Yu; Ding, Cong; Liu, Zhan-Chao; Wang, Liu-Ye; Wang, Yang-Kai
Highlights: Crack width and deflection of BFRP bar reinforced Eco-HDC beam are measured. Effects of BFRP bar diameter, cover thickness and loading regime are considered. Maximum crack width and peak deflection are predicted by formulas in design codes. Governing parameters for serviceability limit states of flexural member are advised. Abstract: Ecological high ductility concrete (Eco-HDC) has a larger tensile deformation than normal concrete, and Eco-HDC can be used to cast bridge deck link slab in negative moment zone. To acquire the flexural design method of bridge deck link slab made by BFRP (basalt fiber reinforced polymer) bar reinforced Eco-HDC, serviceability limit states of beam containing crack width and deflection are studied through the experimental and theoretical analysis. Test variables are diameter of BFRP bar, cover thickness and loading regime. Increasing the BFRP bar diameter or decreasing the cover thickness is an efficient method to decrease the maximum crack width. Cyclic loading type is also beneficial to reduce the maximum crack width. Besides, as the diameter increases, the peak deflection increases within a diameter of 8 mm ∼ 12 mm, and then decreases. Beam with a larger cover thickness has a lower peak deflection. Peak deflection is independent on the loading regime. Formulas in design codes are adopted to predict the maximum crack width and peak deflection, and the formulas are proposed to evaluate the test results. In addition, maximum crack width limit, maximum limit of stress and strain in Eco-HDC and BFRP bar are the governing parameters to compute the reinforcement ratio of BFRP bar in the design of bridge deck link slab.